2012
DOI: 10.4103/1658-354x.105870
|View full text |Cite
|
Sign up to set email alerts
|

Combined general-epidural anesthesia with continuous postoperative epidural analgesia preserves sigmoid colon perfusion in elective infrarenal aortic aneurysm repair

Abstract: Background:In elective open infrarenal aortic aneurysm repair the use of epidural anesthesia and analgesia may preserve splanchnic perfusion. The aim of this study was to investigate the effects of epidural anesthesia on gut perfusion with gastrointestinal tonometry in patients undergoing aortic reconstructive surgery.Methods:Thirty patients, scheduled to undergo an elective infrarenal abdominal aortic reconstructive procedure were randomized in two groups: the epidural anesthesia group (Group A, n=16) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(30 reference statements)
1
0
0
Order By: Relevance
“…The first exhaust time and adverse reaction incidence in group A were significantly lower than those in group B, which indicated that compared with general anesthesia combined with intravenous analgesia, the recovery rate of gastrointestinal tract is faster and safer compared to epidural anesthesia combined with epidural analgesia. Panaretou et al (21) have studied the effects of epidural anesthesia and analgesia on gastrointestinal pressure in patients undergoing aortic reconstruction surgery, and have found that epidural anesthesia and analgesia could relieve gastrointestinal pressure, which is consistent with the results in our study. In this study, it was also found that the first exhaust time after epidural anesthesia combined with epidural analgesia was earlier, which indicated that the gastrointestinal tract recovered faster, so the gastrointestinal pressure was also smaller.…”
Section: Discussionsupporting
confidence: 92%
“…The first exhaust time and adverse reaction incidence in group A were significantly lower than those in group B, which indicated that compared with general anesthesia combined with intravenous analgesia, the recovery rate of gastrointestinal tract is faster and safer compared to epidural anesthesia combined with epidural analgesia. Panaretou et al (21) have studied the effects of epidural anesthesia and analgesia on gastrointestinal pressure in patients undergoing aortic reconstruction surgery, and have found that epidural anesthesia and analgesia could relieve gastrointestinal pressure, which is consistent with the results in our study. In this study, it was also found that the first exhaust time after epidural anesthesia combined with epidural analgesia was earlier, which indicated that the gastrointestinal tract recovered faster, so the gastrointestinal pressure was also smaller.…”
Section: Discussionsupporting
confidence: 92%